Rice straw compost used as soilless media for tomato transplant production. - Ali, Hassan Ibrahim; Ismail, Mohd Razi; Mohd. Mokhtaruddin,; Mohd. Saud, Halimi (2001)
Study was conducted to evaluate the use of rice straw compost used alone or in combination with a peat based vegetable transplant media and to determine whether mixture might provide a more appropriate medium compared to rice straw compost or peat mix alone at Commercial Hydroponics Unit, Universiti Putra Malaysia. The results showed significant differences between treaments in EC and pH. However, seed germination at 5 days was inhibited and significantly reduced at 14 days from sowing date with 100. 75 and 50% compost. The results also indicated that 25% compost gave the highest stem length follow by 50% and then 75% compost, whereas. 100% peat and compost decreased plant height with no significant differences between them